Experiments to identify the optimal sound to use in a new sound ball to improve recruitment, retention, health, and wellness for blind and visually impaired tennis players - Roth, J.; Squelch Costa, D.; Roth, S. A.; Rose, C.; Gibbs, R. N.; Liu, K.; Liu-Lopez, I.; Wagle, M.; Proulx, M. J. (Coaching and Sport Science Review, 2023)
Within the sport of Blind and Visually Impaired (BVI) Tennis, the choice of sound is important in locating the ball. We conducted two experiments to choose a sound that will improve the localizability of the ball, in response to a request for new ball development from the International Blind Tennis Association (IBTA). We screened sounds (freesounds.com) for characteristics that the brain best exploits for sound source localization (Risoud et al, 2018). Sample sounds (23) were tested on an outdoor BVI court in a public park using five Bluetooth speakers, and then replicated in an indoor setting; the environments were otherwise naturalistic and unaltered. Blindfolded-sighted participants (n=29) pointed to where they believed sounds originated, by moving an arrow attached to a large protractor. Degree angles were recorded and converted to absolute degree angle error. The standard BVI tennis rattle ball sound resulted in 9.56 degrees of average angular error at a 30-foot distance. After eliminating sounds that 2 or more people either could not hear in either soundscape or that people had degree angle errors over 15 degrees, we discovered a superior localizable sound that resulted in only 4.00 degrees of average angular error at a 30-foot distance.